Assessment of cone beam computed tomography image quality and dose for commonly used pre-sets in external beam radiotherapy. (October 2022) - Al-Kabkabi, Abdullah; Ramachandran, Prabhakar; Aamry, Ali; Tamam, Nissren; Abuhadi, Nouf H.; Johary, Yehia; Aamri, Hussin; Sulieman, Abdelmoneim; Trapp, Jamie
Abstract: Image-guided radiation therapy (IGRT) adds an additional imaging radiation dose to existing levels of therapeutic radiation. The extra radiation dose received by organs from multiple conae beam computed tomography (CBCT) scans can increase the probability of the secondary cancer risk. In this study, an effort has been made to assess CBCT dose and image quality for standard pre-sets defined for different organs namely, the chest, pelvis, brain, head and neck, and abdomen. The second goal was to investigate whether the radiation dose could be reduced while still achieving high image quality. Image quality was evaluated on the CatPhan Model 503 (Phantom Lab, NY), while organ kV- CBCT doses were evaluated using an Unfors device (Fluke Biomedical) to provide representative measurements for clinical settings. Nominal CBCT projections with reduced exposure times were reconstructed in 3D using the Unfiltered and Filtered-back Projection algorithms. Patient organ dose (mGy) per procedure for brain, chest, pelvis, abdomen, and head and neck were 7.9, 35.3, 28.1, 58.3, and 0.77, respectively. The experimental analysis suggests that adequate image quality could be obtained while decreasing the number of radiographic projections. Reducing the number of the radiographic projections will reduce the scan time and therefore the imaging dose. The proposed method provides an opportunity to reduce the organ doses comparatively lower than the standard CT doses for head and body protocols. The study provides a framework for delivering low radiation doses to critical organs with no risk of long-term exposure. Highlights: This study has successfully quantified CBCT doses for some critical organs. Image quality and radiation dose were evaluated during CBCT. Adequate image quality could be obtained while decreasing the number of radiographic projections. The study provides a framework for delivering low radiation doses to critical organs with no risk of long-term exposure.